Intelligentsia and Politics - Rapoportas, Sergejus (Sociologija. Mintis ir veiksmas, 2006)
The article is dedicated to contemporary political situation in Lithuania, emphasizing sociopsychological content of the opposition between different political competitors in modern Lithuania. The article emphasizes the role of intelligentsia as the basic group of politicians, its’ forms, intentions of their political activity, and, especially, the motive of their „self-importance“. This competetive activity has moral „cover“, opponents reveal each other, using the fact, that under the cover of popular slogans they satisfy their own needs and values. As a result, a morality occurs a kind of tool in political game.